Revisiting Renewable Energy and Foreign Direct Investment: Paradoxical Impacts on Ecological Footprint - Osabohien, Romanus; Akpa, Armand Fréjuis; Zogbasse, Symphorien; Jaaffar, Amar Hisham; Al-Faryan, Mamdouh Abdulaziz Saleh; Albert, Olalekan Paul; Orole, Felix (International Journal of Energy Economics and Policy, 2026)
This research analyses the influence of foreign direct investment (FDI) and renewable energy usage on China's ecological footprint from 1990 to 2022, employing the Autoregressive Distributed Lag (ARDL) model. The findings indicate that, in the short-term, a 1% increase in renewable energy consumption raises the ecological footprint by 0.022 global hectares (gha) per capita. However, in the long-term, this increase is more pronounced, augmenting the footprint by 0.033 gha per capita. Moreover, foreign direct investment (FDI) exhibits a significant negative relationship with the ecological footprint in the short-term, indicating that such expenditures facilitate environmental enhancements. Nonetheless, over the long term, foreign direct investment does not exert a statistically significant influence on China's ecological footprint. These findings contest traditional assumptions about the environmental advantages of renewable energy and underscore the necessity for improved regulations that optimise renewable energy practices. The study's findings indicate the necessity of encouraging green foreign direct investment to maintain its immediate environmental advantages. Recommendations include diversifying energy sources, strengthening environmental regulations, and integrating technological innovation in FDI-driven sectors to foster long-term sustainability. The paper concludes with recommendations for further research, including sectoral analysis, comparative studies, and the examination of environmental policies in reducing the ecological footprint.